EVALUASI POTENSI WISATA BERMI ECO PARK (BEP) SEBAGAI PENOPANG PEREKONOMIAN MASYARAKAT - Tutiil Khoiroh; Kurnia Maulidi Noviantoro; Nining Winarsih (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
The purpose of this study is to describe and identify potentials that are not yet optimal in the development of Bermi Eco Park (BEP). This research use desciptive qualitative approach. Data was collected through the methods of observation, interviews, and documentation. The data analysis technique is through stages; data reduction, data modeling, data classification and drawing conclusions. The research findings explain that the existence of the Bermi Eco Park (BEP) destination has a good impact on improving the economy of the surrounding community. The existence of the Bermi Eco Park (BEP) makes the community play an active role in seizing opportunities to increase income. Despite the fact that they only take advantage of the existence of tourist destinations to earn additional income. The recommendations for optimizing the potential of Bermi Eco Park (BEP) include; (1) the need for additional outbound rides; (2) reforestation with environmental concepts in certain areas; (3) digitizing visitors with barcodes; and (4) the need for visitor restrictions in order to maintain environmental balance.Key word: Potency; Economy; Bermi Eco Park(BEP).